Preparation and characterization of poly(ethylene terephthalate) films coated by chitosan and vermiculite nanoclay. (1st December 2018) - Essabti, Fatima; Guinault, Alain; Roland, Sébastien; Régnier, Gilles; Ettaqi, Saïd; Gervais, Matthieu
Highlights: Poly(ethylene terephthalate) (PET) 130 μm thick films have been successfully coated with 1–3 μm thick of homogeneous layers of chitosan or vermiculite/chitosan nanocomposite (with 0–50 wt% of vermiculite). Improvement of the Barrier improvement factor (Bif) of a PET film of 100 in helium with a 2.40 μm thick chitosan/vermiculite (50 wt%) layer. Decrease in the oxygen transmission rate from 0.36 to 0.016 cm3/m2.day with addition of 40 wt% of vermiculite to chitosan layers. Permeability of nanocomposite layers are two decades lower than poly(vinylidene chloride) (PVDC) in dry condition. Abstract: Chitosan (CS) layers are coated on a poly(ethylene terephthalate) (PET) film in order to decrease the oxygen permeability through the polymeric films for food packaging applications. Oxygen transmission rate (OTR) of the 130 μm PET films can be decreased from 11 to only 0.31 cm 3 /m².day with a coated layer of 2 μm of CS. Additional decrease is obtained with the addition of vermiculite (VMT) to CS matrix in high proportion (40 to 50 w/w%). The OTR of the coated PET films decreased to very low values, below the detection limit of commercial instrumentation (≤0.008 cm 3 /m 2 day). This high-barrier behavior is believed to be due to the brick wall nanostructure, which produces an extremely tortuous path for oxygen molecules.